Penggunaan Natrium Silikat pada Proses Pelorodan Batik Terhadap Pelepasan Lilin dan Kekuatan Tarik Kain - Dwi Suheryanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
Wax removing batik cloth with synthetic dye can use starch, soda ash, and a mixture of both. The use of cassava starch perfection to release wax batik less than the maximum, medium soda ash will reduce the intensity of the color. The purpose of this study was to determine the extent of the effect of the use of sodium silicate in the process of batik wax removing percentage of the wax off and tensile strength fabric. As the research object, using a type of cotton fabric primisima with canting seal, then dyed with napthol dyestuff, then removing. Variations in the concentration of sodium silicate in the process wax removing is 1, 2, 3, and 4 g/l, respectively, at a temperature of 80-90 ° C. The result of the study showed, that the use of sodium silicate concentrations were increased until the optimal limit a reduction in the strength of the fabric, both warp and weft direction. Medium weight percentage wax-similar results regardless show, which increased with increasing concentrations of sodium silicate is used. From the results of the analysis revealed that there was no significant difference in tensile strength test and wax off against the use of sodium silicate concentration on wax removing process. Economical to use, sodium silicate with a concentration of 1 g/l is recommended for use in the process of batik cloth wax removing cotton, wax off result percentage 97.686%, a decrease in the tensile strength of the warp direction by 0.46%, 0.66% feed direction, a decrease in intensity color 4%, the cost of production of cloth per sheet IRD 4,650.